Customer relationship management strategy in Starbucks card optimization in the Pandemic era - Munifa, Hartoyo (Universitas Malikussaleh, 2022)
Marketing communication is important, in this case paying attention to Customer Relationship Management. The number of companies that are currently competing fiercely has become a trigger for Starbucks Indonesia to maintain the loyalty of existing customers because the competition is quite tight from competitors considering that this company is engaged in the food and beverage sector which means maximum service and quality of products delivered to customers. In this era of pandemic, Starbucks ' card strategy is very profitable and makes it easier for customers to order drinks or food online. The existence of loyal customers is evidenced by the use of the Starbucks Card, so the purpose of this study is to determine the Customer Relationship Management Strategy in Optimizing the Starbucks Card in the Pandemic Era. This study used a qualitative approach and data collection techniques were carried out through interviews and document studies. For data collection techniques, the authors conduct interviews and view related documents which later the information obtained will be equated with the theory that the author uses in this study, namely Customer Relationship Management Theory and Loyalty Theory.